Tribological behaviour of orthodontic archwires under dry and wet sliding conditions in-vitro. II - Wear patterns - Berradja Abdenacer; Willems Guy; Celis Jean-Pierre (Sciendo, 2023)
To evaluate the wear patterns of orthodontic archwires in dry and wet conditions in-vitro.